Crosslink in bone collagen in Paget's disease. - Misra, D P (1975)
The crosslink in bone collagen was analysed in specimens of bone obtained at necropsy from cases of Paget's disease and compared with normal bone collagen of the same age. The specimens were stored at -20 degrees C before analysis. The predominant crosslink in a normal bone collagen was hydroxylysinohydroxynorleucine (di OH-LNL) (F1), which was designated syndesine in the past; another fraction, hydroxylysinorleucine (HLNL) (F2), musch less prominent than di OH-LNL, was also noted in a normal bone collagen. Both fractions were reduced in bone tissue of advancing age. The peak corresponding to HLNL was considerably increased in Paget's disease. This abnormality was constantly seen in specimens of bone from cases of Paget's disease, but the significance of the finging could not be assessed from the present investigation. Calcitonin has been shown to produce complete remission in Paget's disease and the crosslink pattern was found to be normal in specimens examined froma calcitonin-treated patient. This shows that calcitonin has some effect on the metabolism of collagen and a normal crosslink in such a situation lends support to this idea.